The Role of Archives in Managing Public Information in the East Java Province Library and Archives Service - Arbain, Fayola Nur Khasia (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
The role of archives in managing public information has become an urgent need, both for the government and society. The East Java Province Library and Archives Service plays a strategic role in utilizing archives to support solving public problems, both in the legal field, preserving historical traces, and providing public information related to state administration. Aims to explain the role of archives in public information using a qualitative descriptive approach through in-depth interviews with relevant employees. The results show that archives play a determining role in resolving public problems, serve as a Collective Memory of the Nation that preserves historical and cultural heritage, and as a provider of transparent information to support the accountability of state administration and legal entities. Optimizing archive management, including through digitization and increasing accessibility, is expected to improve the quality of public information services and strengthen the role of archives in meeting the needs of society as a whole.